Evaluation of Consumption Pattern and Microflora Reflection on Phase II Laying Hens with Free Feeding Choice - Sigit Handoko; Suhardi Suhardi; Eudia Christina Wulandari (Tropical Animal Science, 2020)
The aim of this study to determine effect of free feeding choice on consumption and profile of BAL on intestinal small & large of second phase laying hens. The research was conducted in June – July 2020 at Sidoharjo, Sumbung, Cepogo, Boyolali . This study used thirty of Lohmann Brown laying hens, 52 weeks . Feedstuffs used in this study are corn, rice bran and layer concentrate . Data analysis was measured by quantitative with graphs. This results showed that phase II on laying more consumped corn than rice bran and concentrate. Average of consumtion corn’s are 80 g/ hens/ day . However , the average of ration consumtion are 10 g / hens / day .On this study compare that hens more consume corn than consentrate , approximatly ,161 g/hens/ dayfor corns and 28 g /hens /day for consentrate . The microflora condition of the small and large is dominated by gram-positive bacteria, such as Bacillus, ( with contained are Diplobacillus, Streptobacillus and Streptococcus bacteria. The conclusion of this study was that Free Feeding Choice method can improve the health of the digestive tract and increase productivity of laying hens.